MODEL PENGARSIPAN MUSEUM SENIRUPA - Syamsiar, Syamsiar (Institut Seni Indoensia Surakarta, 2010)
This research tried to expose a model which is affiliated to the maintainance of fine art collections through the archives pattern. Archival models was the one of severals possibilities which is useful for the collections in any object. According to the main focus, this research identified some samples in the fine art collections related to the museum management and its urgency in their public interest. For this reason some comparative archival models will be referred from Bentara Budaya Yogyakarta and other established archival model. The database models was also referred to the comparative archival models. This article will expose empirical data from archival models to bring up the best choice of museum management. Keywords: archives, models, museum of fine art.